Psychometric properties of Toulouse Self-Esteem Scale-Adolescent Edition "A Field Study in the City of Lattakia" - Boubou, Mounzer; Zmourod, Amira (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aims to extract the psychometric properties of the Adolescent edition of Toulouse self-esteem scale. The scale was translated from French to Arabic and it was introduced to a set of Arabic language specialists to ensure good paraphrasing, and then it was back-translated to the original language (the French) to ensure the accuracy of the translation. The Scale was implemented on a random sample consisting of 466 adolescents in Lattakia city. The study results indicate a high level of validity of the scale and high degree scale of reliability identical with the statistical indicators to of the French version of the scale. Subsequently, hypothesis were tested to check whether there is a difference between male and female scores on the scale. Differences in the dimension of the social self were found. The research concluded to suggest the need for further studies on the scale in different environments and the need of using it in educational and psychological fields.